Challenges of classical poetry with government institutions (up to the sixth century) - اسماعیل شفق (تاریخ ادبیات)
Persian qasidas contain the way of thinking, livelihood and behavior of poets. And on the other hand, it is considered a reflection of the tastes and actions of the past rulers. The history of Persian poems from the Samani era to the 6th century can be studied from different perspectives. But one of the topics that can be researched about the poems of this historical period is the examination of the challenges that poets had with government institutions. On the one hand, the poets of this period needed the financial support of the rulers, on the other hand, the rulers needed the artistic abilities of the poets to spread the fame of their dominance and power to others. In this two-way interaction, sometimes we come across poets who have not sacrificed their freedom and rights for the sake of fame and fortune, but the majority of the old ode poets had reached some sort of agreement with the power centers and in that form, they played a role as propaganda speakers for the power holders. This research aims to examine the challenges of ancient poetry from various social, moral and political perspectives. Therefore, it has researched one of the most important historical periods in terms of the peak of odes, that is, from the Samani era to the sixth century.